Arthur in a pickle - Brown, Marc Tolon (New York : Random House, 1999)
After lying about what happened to his homework, Arthur has such a bad dream about being "in a pickle" that he decides to tell the truth.
"Two pages of stickers in book."
Keywords: Aardvark -- Fiction; Homework -- Fiction; Honesty -- Fiction; Pickles -- Fiction